A phytosociological survey of the main plant community types of alpine and sub-alpine belt in the Sibillini Mountains (Central Apennines, Italy) - Costanzo, Emanuele; Furnari, Francesco; Tomaselli, Valeria (Lazaroa, 2010)
The vegetation communities of the alpine and subalpine bioclimatic belts of Sibillini Mountains were investigated following the phytosociological approach. During fieldwork 108 relevés were collected. The vegetation of grasslands and pastures, screes, talus slopes and high altitude rock faces was investigated, identifying several phytosociological types within the following alliances: Seslerion apenninae (Elyno-Seslerietea) with the two suballiances Seslerenion apenninae and Leontopodio nivalis-Elynenion myosuroidis, Ranunculo pollinensis-Nardion strictae (Nardetea strictae), Phleo ambigui-Bromion erecti with the suballiance Brachypodenion genuensis (Festuco-Brometea), Arction lappae (Artemisietea vulgaris), Saxifragion australis and Cystopteridion fragilis (Asplenietea trichomanis), Linario-Festucion dimorphae (Thlaspietea rotundifolii). Raw data from 63 relevés, regarding the vegetation of grasslands and pastures, was subjected to multivariate analysis. The main structural and ecological characteristics of these communities are shown in this paper. The study showed strong similarities with the high altitude vegetation of the Majella and Gran Sasso massif.